Case report: Acute hepatic failure secondary to metastatic LIVER'S infiltration by upper tract urothelial carcinoma. (September 2019) - Serra, Francesco; Guidetti, Cristiano; Spatafora, Francesco; Cabry, Francesca; Farinetti, Alberto; Mattioli Anna, Vittoria; Gelmini, Roberta
Abstract: Introduction: Acute liver failure (ALF) secondary to malignant infiltration of the liver from urothelial carcinoma is a very rare clinical condition and is often diagnosed only after death. Upper tract urothelial carcinoma (UTUC) is a rare, from 5% to 10% of all urothelial tumours, but possible cause of ALF when there is extensive liver metastatic involvement. We report the case of a patient who died in the intensive care unit (ICU) of our hospital from multiple organ failure (MOF) secondary to ALF, as a result of infiltration of the liver from UTUC diagnosed after surgery. PRESENTATION OF THE CASE: A 69-year-old Caucasian man was referred to our hospital for hematuria, melena, right upper quadrant (RUQ) pain and jaundice developed over the previous two weeks. After multidisciplinary discussion, he underwent emergency exploratory laparotomy to perform cholecystectomy because of suspected acute cholecystitis considered as a septic focus within the left kidney. He developed MOF and died on the 6th postoperative day. Discussion: From the diagnosis of the renal mass and the death of the patient, a few days have passed, and the diagnosis of UTUC has been put only at histological examination.The most common sites of metastases from UTUC are lymph nodes, lungs, liver, bones and peritoneum. Moreover, liver metastases have been identified to have an independent negative impact on overall survival in a patient affected by UTUC. Conclusion: The authors suggest that this condition should be taken into account when dealing with patients with evidence of a renal mass and simultaneous ALF. Highlights: Unusual clinical presentation of acute liver failure from upper urothelial carcinoma (UTUC). Rarely these diseases are managed in the emergency setting. This condition should be taken into account when dealing with patients with evidence of a renal mass and simultaneous ALF.